ASSESSMENT THE POST OPERATIVE COMPLICATION AMONG PATIENTS WITH GENERAL ANESTHESIA - Kareem, Mariam Mohammed Ali; Ali Fadel Abbas; Yassien, Nada Jassem; Thuraya Ali Baseer; Layla Raheem Hakem (PT. Antis International Publisher, 2025)
Objective: Each year, increasing numbers of people are undergoing surgery. Many of these patients are older and have multiple comorbidities. General anesthesia is very common anesthetic procedure which is used in several surgical approaches. Without general anesthesia many of these surgeries are lifesaving or life-changing and would not be possible. But all medical procedures are associated with some complications, even when they are performed by experts. The severity and rate of these complications depend on patient's state of health. Method: A Descriptive quantitative design study has been used in the present study to estimate the Post operative complication among patient undergo the general anesthesia at Al-Sadder Medical City and Al-Hakeem hospital during the October,15th, 2023 to March,28th ,2024. Results: According to the current study sample researcher found the most common complication in the respiratory system was difficult breathing (50%). Regarding Gastrointestinal complications recent study showed that the highest percentage were nausea (71.0%), constipation (68.33%) and vomiting (58%). The highest percentages of complication in the cardiovascular system was hypotension (41.7%). There is low percent in urinary incontinence and dysuria with (20%) and (16.67%). Regarding to the general complications the result show that headache is the most common with (82%) from all sample. Novelty: Most of precent study sample were diabetic patient (66.7%), those with previous surgery (66.7%), those with only one previous surgery (25%), the most complication after general anesthesia were Headache, Nausea, Chills, Constipation Motor deficit. And there is no correlation between patient who had previous surgery and who had not.